PSIKOEDUKASI ISLAMI TERHADAP KEDISIPLINAN SANTRI DALAM MENJAGA PRIVASI DIRI DAN ORANG LAIN DI LINGKUNGAN PESANTREN NURUL CHOTIB JEMBER - Callista Anna Khumaidah Salmah; Abd. Syakur; Muflikhatul Khoiroh (STAI Pelabuhan Ratu, 2025)
This study aims to increase students' awareness of the importance of maintaining their modesty (awrat), a sense of shame (al-ḥayā’), and respecting the privacy of others within the Nurul Chotib Jember Islamic Boarding School environment through an Islamic-values-based psychoeducational approach. Initial observations indicate that some students still habitually leave their rooms without wearing a hijab and open or borrow friends' belongings without permission. These habits are considered normal because they have been passed down from generation to generation from senior students. This study used a descriptive qualitative method using observation, interviews, and documentation techniques with 42 junior high school (SMP/MTs) students. Psychoeducation was implemented through material delivery, discussions, case studies, and reflections that integrated Quranic verses, Hadith, and the concept of Islamic etiquette. The results showed an increase in students' understanding and behavioral changes after participating in the psychoeducational activities, particularly in terms of discipline in wearing the hijab, asking permission before borrowing items, and reminding each other about etiquette and social etiquette. Psychoeducation has been proven effective in fostering moral awareness by instilling spiritual meaning and Islamic values ​​behind Islamic boarding school rules. This research is expected to serve as a basis for developing more sustainable and contextual character development programs for students in Islamic boarding school environments.